Sequence requirements for the export of the Plasmodium falciparum Maurer's clefts protein REX2 - Silvia Haase; Susann Herrmann; Christof Grüring; Arlett Heiber; Pascal W. Jansen; Christine Langer; Moritz Treeck; Ana Cabrera; C. Bruns; Nicole S. Struck; Maya Kono; Klemens Engelberg; et al. (2008)
A short motif termed Plasmodium export element (PEXEL) or vacuolar targeting signal (VTS) characterizes Plasmodium proteins exported into the host cell. These proteins mediate host cell modifications essential for parasite survival and virulence. However, several PEXEL-negative exported proteins indicate that the currently predicted malaria exportome is not complete and it is unknown whether and how these proteins relate to PEXEL-positive export. Here we show that the N-terminal 10 amino acids of the PEXEL-negative exported protein REX2 (ring-exported protein 2) are necessary for its targeting and that a single-point mutation in this region abolishes export. Furthermore we show that the REX2 transmembrane domain is also essential for export and that together with the N-terminal region it is sufficient to promote export of another protein. An N-terminal region and the transmembrane domain of the unrelated PEXEL-negative exported protein SBP1 (skeleton-binding protein 1) can functionally replace the corresponding regions in REX2, suggesting that these sequence features are also present in other PEXEL-negative exported proteins. Similar to PEXEL proteins we find that REX2 is processed, but in contrast, detect no evidence for N-terminal acetylation.